Celebrating Brett Dorian's 41st Birthday - Watkins, Howard K. (1975)
Front: Bob Higgins, Ray Starks, Ruben Lucero, Virginia Salmeron, Alice Gutierrez, Mary Ludy, Doris Burnes, ?; Back, Al Berryman, Chuck Kahill, Elaine Harris, William Leifer, Gloria Escalante, Brett Dorian, Howard Watkins